Screening for Methanol-Utilizing Yeasts Having Methyl formate-producing activity = Seleksi Khamis pengguna Metanol yang mampu menghasilkan Metil Format - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
Methanol-utilizing yeasts were screened for methyl formate- producing activity. Eleven strains out of twenty strains of yeasts tested were found to have the activity. Pichia methanolica showed the highest activity, followed by Candida sp. N-16, Candida sp. 1 -B, Pichia pinus, and Candida sp. 25-A, respectively. Methyl formate was found to accumulate in the cultural media of those strains during the course of the their growth in methanol- containing media. Along with the methyl formate-producing activity it wasfoundthat resting cells also had a hydrolyzing |activity against methyl formate. Cultivation and reaction conditions were optimized with respect to methyl formate production. The methyl formate-producing activity was strongly induced by methanol but weakly induced by glycerol. On the other hand, the methyl formate-producing activity was not induced by ethanol and glucose. However, methyl formate- hydrolyzing activity was induced by methanol, glycerol, glucose, and ethanol although with different intensities.